Acute exposure to deoxynivalenol inhibits porcine enteroid activity via suppression of the Wnt/β-catenin pathway. (1st May 2019) - Li, Xiang-Guang; Zhu, Min; Chen, Ming-Xia; Fan, Hong-Bo; Fu, Hou-Long; Zhou, Jia-Yi; Zhai, Zhen-Ya; Gao, Chun-Qi; Yan, Hui-Chao; Wang, Xiu-Qi
Highlights: A reliable system for cultivation of porcine enteroids is established. Acute exposure to deoxynivalenol suppresses the activity of intestinal stem cells. Wnt/β-catenin pathway participates in deoxynivalenol-induced intestinal stem cell damage. Abstract: The intake of food containing deoxynivalenol frequently causes damage to the intestine, the renewal of which is driven by intestinal stem cells (ISCs). Nevertheless, the toxicity of deoxynivalenol on ISCs and its underlying mechanisms remain to be elucidated. As pigs are the most sensitive animals to deoxynivalenol, we used piglets for investigation in this study. Here, we show that intestinal epithelial cell activity, B cell-specific Moloney murine leukemia virus insertion site 1 (Bmi1) protein level, and Wnt/β-catenin pathway activity were suppressed with acute expose to deoxynivalenol. We further established a novel system for porcine crypt isolation and ex vivo cultivation. Crypts and crypt cells expanded and budded with typical enteroid morphologies under this system. Our results show that both acute in vivo and in vitro administration of deoxynivalenol significantly decreased enteroid activity. Simultaneously, protein levels of β-catenin and leucine-rich-repeat-containing G-protein-coupled receptor 5 (Lgr5) in enteroids were reduced by deoxynivalenol exposure. In conclusion, we established a reliable culture system for porcine enteroids and demonstrated for the first time that the activity of ISCs and the Wnt/β-catenin pathway is sensitively suppressed by acute deoxynivalenol exposure.